EFEKTIVITAS PEMUNGUTAN PAJAK REKLAME DANKONTRIBUSINYA TERHADAP PAJAK PENDAPATAN ASLI DAERAH(PAD) DI KOTA SURABAYA - CHIDYASARI, NURULIA (Jurnal Akuntansi AKUNESA, 2017)
Taxes on billboard advertising is a potential income source of Surabaya to support the economic development of the city of Surabaya. The purpose of this research is to measure the level of effectiveness of advertisement taxation in Surabaya. This research was conducted at the Regional Revenue Office of Surabaya. By using descriptive method and secondary data, I find that the percentage of tax effectiveness is more than 100% in 2012 and 2014 and the lowest effectiveness percentage was in 2011, that is 75.19%. The advertisement tax for contributions in 2010 amounted to 18.78% and the lowest in 2013 at 13%. Keywords: advertisement tax, real district income, effectiveness, contribution